Pengaruh Motivasi dan Budaya Organisasi terhadap Komitmen Organisasi dalam Meningkatkan Kinerja Pegawai pada Dinas Sosial, Pengendalian Penduduk, dan Keluarga Berencana, Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Bungo - Suci Aryusie; Pantun Bukit; M. Zahari (J-MAS (Jurnal Manajemen dan Sains), 2023)
The research was conducted with the aim of finding out the description of the condition of motivation, organizational culture and employee performance at the Social Service, KB, P3A Bungo Regency, motivation and organizational culture through organizational commitment to employee performance at the Social Service, KB, P3A. The object of this research is the Social Service, Family Planning, P3A of Bungo Regency. Using census techniques, the number of respondents in this research was 61 people. This research produces information that (1) Motivation has a direct influence on work commitment. (2) Organizational culture does not have a direct influence on Work Commitment. (3) Simultaneously motivation and organizational culture have an influence on employee work commitment at the Social Service, Family Planning, P3A. (4) Organizational motivation has a direct influence on performance. (5) Organizational culture has no direct effect on performance. (6) organizational commitment is very strongly influenced by motivation and organizational culture. (7) organizational commitment influences organizational performance. (8) Organizational commitment does not have a motivational influence in increasing employee performance. (9) Organizational commitment does not influence organizational culture in increasing employee performance. (10) simultaneously motivation, organizational culture and organizational commitment have no effect on employee performance.